Process Innovation : reengineering work through Information Technology - Davenport, Thomas H. (Boston, 1993)
The business environment of the 1990s demands significant changes in the way we do business. Simply formulating strategy is no longer sufficient; we must also design the processes to implement it effectively. The key to change is process innovation, a revolutionary new approach that fuses information technology and human resource management to improve business performance. The cornerstone to process innovation's dramatic results is information technology a largely untapped resource, but a crucial "enabler" of process innovation. In turn, only a challenge like process innovation affords maximum use of information technology's potential. Davenport provides numerous examples of firms that have succeeded or failed in combining business change and technology initiatives. He also highlights the roles of new organizational structures and human resource programs in developing process innovation. Process innovation is quickly becoming the byword for industries ready to pull their companies out of modest growth patterns and compete effectively in the world marketplace.
Keywords: Information technology